The Economic Feasibility of Sweet Potatos Farming by Using Selected N Fertilization - Dian Adi Anggraeni Elisabeth; Erliana Ginting; Joko Restuono (Publisher of Widyagama University of Malang (UWG Press), 2018)
Sweet potato is normally cultivated in wet land after rice or in dry land during rainy season. N fertilization is commonly applied to increase sweet potato yield. Therefore, the economic feasibility of using selected N fertilizer in sweet potato farming in dry land was studied. Three improved varieties, namely Jago (white-fleshed), Beta 2 (orange-fleshed), and Antin 2 (purple-fleshed) were grown at the Experimental Station of Muneng, East Java and treated with six N fertilization as follows: F1= 0 N fertilization as a check; F2= 50 kg/ha of Urea; F3= 100 kg/ha of Urea; F4= 100 kg/ha of ZA; F5= 200 kg/ha of ZA; and F6= 5,000 kg/ha of manure. The treatment is assumed to be economically viable if the value of Marginal Benefit Cost Ratio (MBCR) is greater than 1. The results showed that the combination of F2 with Beta 2, F3 with Antin 2, and F5 with Beta 2 were viable with the MBCR value of 17.13, 25.85, and 11.61, respectively. Although the data was limited, the study tentatively concludes that profitable N fertilization for sweet potato farming considerably depends on differences in yield, N fertilizer source and dose, as well as selling price of particular variety.JEL Classification: C93, D24, Q12